Prognosis following long term splint use in horizontal root fracture: case report - Gizem İnan; Alev Alaçam (Gazi University, 2017)
Introduction: Root fracture of the incisors is a rare condition in dental trauma. It can be treated successfully by stabilizing the repositioned tooth fragments. In splint applications it is recommended to use flexible or semi-rigid splints for 4 weeks; use of splints for extended durations may increase the risk of external root resorption. Case Report: A 12-year-old male patient who had had a dental trauma 10 months earlier consulted the Department of Pediatric Dentistry, Faculty of Dentistry at Gazi University. In his intraoral examination, mobility was detected in the mandibular right central incisor tooth. After clinical and radiographic examination, the patient was diagnosed with horizontal root fracture and the fractured tooth was splinted. The patient did not attend the scheduled follow-up visits, but re-appeared 2 years later for the removal of the splint. One year after the removal of the splint, healing with calcified tissue was observed. Conclusion: Although it is known that long-term splint causes root resorption, in this case it was observed that no pathology developed, and healing with calcified tissue occurred after splint use for an extended period. This is contrary to what has been argued in the literature.